تصميم معايير الكترونية لتقييم الأستاذ الجامعي بغرض تحسين الأداء ورفع الكفاءة - د سيف الدين فتوح; الصادق محمد آدم (White Nile Journal for Studies and Research, 2015)
Means and methods of evaluation are used in various fields of life. in institutions organizations and governmental bodies. Evaluation has an effective impact on improving the role of these institutions. In different countries. universities and higher educational institutes spare no effort to improve their staff performance by using follow up teaching practice and evaluation. There are also some common methods to achieve evaluation tasks such as evaluation through college's deans. heads of deportments and partners or by urging the teacher to assess himself through providing the necessary scientific and educational tools. in addition to that students' assessment can be used which is believed to be the most stable method in evaluating performance professionally and technically.